2006
DOI: 10.1200/jco.2005.04.8561
|View full text |Cite
|
Sign up to set email alerts
|

The Ongoing Search for the Sources of the Breast Cancer Survival Disparity

Abstract: In the search for explanations for the persistent disparity in outcomes after breast cancer diagnosis between African American and white American women, there has always been something of a divide in the research community. Social and economic differences between the groups are too glaring to ignore, and have significant health consequences across a spectrum of diseases, including cancer. On the other hand, in a disease as heterogeneous as breast cancer, biology is destiny, in ways that we sometimes understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Although African American women have a lower incidence of breast cancer than Caucasians, repeated studies have shown that they suffer from more aggressive disease characterized by diagnosis at an earlier age, later stage, higher grade, and greater mortality [14]. While socioeconomic factors contribute in part to this disparity in survival, they do not account for all differences noted between these two racial groups [3, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Although African American women have a lower incidence of breast cancer than Caucasians, repeated studies have shown that they suffer from more aggressive disease characterized by diagnosis at an earlier age, later stage, higher grade, and greater mortality [14]. While socioeconomic factors contribute in part to this disparity in survival, they do not account for all differences noted between these two racial groups [3, 5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Black female patients are more frequently diagnosed with late-stage breast cancer than white patients [4,26], even though they generally have similar rates of mammographic screening [27]. When differences have been found in mammographic screening rates, they do not satisfactorily explain later-stage diagnosis among black women [28,29].…”
Section: Biomedical and Sociomedical Factors In Black–white Patient Dismentioning
confidence: 99%
“…4 Despite extensive study of socioeconomic status, race, age, ethnicity and body mass index among others, no factor has emerged as a single dominant predictor. [4][5][6][7][8][9] Commonly, these patients are labeled by clinicians as members of two groups: noncompliant patients or patients with limited access to care. We postulate that a third patient group exists: those lost within the healthcare system who make frequent provider contacts and yet evade the network of preventative services, increasing their likelihood of late diagnosis.…”
mentioning
confidence: 99%